2012
DOI: 10.1007/s10207-012-0154-9
|View full text |Cite
|
Sign up to set email alerts
|

Authentication in mobile devices through hand gesture recognition

Abstract: This article proposes an innovative biometric technique based on the idea of authenticating a person on a mobile device by gesture recognition. To accomplish this aim, a user is prompted to be recognized by a gesture he/she performs moving his/her hand while holding a mobile device with an accelerometer embedded. As users are not able to repeat a gesture exactly in the air, an algorithm based on sequence alignment is developed to correct slight differences between repetitions of the same gesture. The robustnes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
39
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(39 citation statements)
references
References 30 publications
0
39
0
Order By: Relevance
“…Guerra-Casanova et al [15] proposed a biometric technique based on the idea of authenticating a person on a mobile device by gesture recognition, and achieve Equal Error Rate (EER) between 2.01% and 4.82% on a 100-users base. Unobtrusive methods for authentication on mobile smart phones have emerged as an alternative to typed passwords, such as gait biometrics (achieving an EER of 20.1%) [13,26], or the unique movement users perform when answering or placing a phone call (EER being between 4.5% and 9.5%) [11].…”
Section: C) User Authentication By Their Behavior On Touch Screensmentioning
confidence: 99%
“…Guerra-Casanova et al [15] proposed a biometric technique based on the idea of authenticating a person on a mobile device by gesture recognition, and achieve Equal Error Rate (EER) between 2.01% and 4.82% on a 100-users base. Unobtrusive methods for authentication on mobile smart phones have emerged as an alternative to typed passwords, such as gait biometrics (achieving an EER of 20.1%) [13,26], or the unique movement users perform when answering or placing a phone call (EER being between 4.5% and 9.5%) [11].…”
Section: C) User Authentication By Their Behavior On Touch Screensmentioning
confidence: 99%
“…Applications involving the Kinect include static hand gesture recognition [11,24], dynamic hand/arm gesture recognition [33], software control [25], surgeons assistance [15], and authentication [29]. Other sensors employed for (hand) gesture recognition include (smartphone integrated) accelerators [9,10,16], virtual reality interfaces like Cyber Glove [20], and specific biometric devices (e.g. a Smart Pen [1]).…”
Section: Introductionmentioning
confidence: 99%
“…Arm movements are captured for this purpose by (smartphone integrated) accelerators [9,10,16]. Mid-air handwriting recognition for authentication is conducted with different sensors (Kinect [29], Bio Smart Pen [1]); sign language recognition for identifying user-specific pass-codes is suggested in [12].…”
Section: Introductionmentioning
confidence: 99%
“…Along with the popularization of various IT devices such as smart phones, Kinect, and stereo cameras, a number of studies have been conducted to show that gestures can be used as a good behavioral biometric signal for user authentication. In earlier studies [1012], it was shown that accelerometer-based gesture recognition is feasible for user authentication in mobile devices. Also, in [13] the accelerometer and the gyroscope on mobile devices were combined for gesture-based user authentication.…”
Section: Introductionmentioning
confidence: 99%